BIOCHAR FROM AGRICULTURAL BY-PRODUCTS IN VIETNAM: A REVIEW OF AN ADSORPTION SOLUTION FOR AMMONIUM AND PHOSPHATE REMOVAL IN WASTEWATER - Minh Thanh Le; Lan Huong Nguyen; Dat Duc Nguyen Duc; Tan Phong Nguyen; Xuan Hoan Nguyen; Huy Hoang Phan Quang; Duy Thanh Pham; Hoang Phuong Nguyen Vu (HUIT Journal of Science, 2025)
Vietnam’s agricultural sector, which plays a pivotal role in ensuring national food security and bolstering the country’s global agricultural export position, faces significant environmental challenges, especially nutrient pollution due to excessive ammonium (NH4+) and phosphate (PO43-) from agricultural practices. While crop residues such as rice straw, husks, and bagasse are generated in vast quantities, they remain largely underutilized, contributing to environmental degradation, including eutrophication of inland water ecosystems. This review examines the potential of agricultural by-products, particularly biochar, as eco-friendly adsorbents to mitigate nutrient pollution. Biochar, produced through the pyrolysis of agricultural residues, has shown significant promise in adsorbing NH4+ and PO43- from wastewater. The study highlights various treatment methods, such as the modification of biochar with metal oxides and other chemical treatments, to enhance its adsorption capacity. This review also emphasizes the feasibility of using these low-cost, locally available materials to develop sustainable solutions for wastewater management in Vietnam, particularly in rural areas where traditional wastewater treatment technologies are often unaffordable or impractical.